2020
DOI: 10.1021/acsnano.0c03286
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Tubustecan Hydrogel as Chemotherapeutic Carrier to Improve Tumor Penetration and Local Treatment Efficacy

Abstract: Local chemotherapy is a clinically proven strategy in treating malignant brain tumors. Its benefits, however, are largely limited by the rapid release and clearance of therapeutic agents and the inability to penetrate through tumor tissues. We report here on a supramolecular tubustecan (TT) hydrogel as both a therapeutic and drug carrier that enables long-term, sustained drug release and improved tumor tissue penetration. Covalent linkage of a tissue penetrating cyclic peptide to two camptothecin drug units cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 80 publications
0
41
0
Order By: Relevance
“…Recently, Wang et al reported the synthesis of an amphiphilic construct in which two camptothecin (CPT) drug units are covalently bound onto a cyclic iRGD peptide through a biodegradable disulfanylethyl carbonate linker (etcSS). 72 This amphiphilic construct selfassembles into tubular supramolecular polymers (SPs) in water and in 3D-HGs in phosphate buffer with a critical gelation concentration ranged between 1.5 and 2 mM (Figure 4…”
Section: Rgd Containing Peptidesmentioning
confidence: 99%
“…Recently, Wang et al reported the synthesis of an amphiphilic construct in which two camptothecin (CPT) drug units are covalently bound onto a cyclic iRGD peptide through a biodegradable disulfanylethyl carbonate linker (etcSS). 72 This amphiphilic construct selfassembles into tubular supramolecular polymers (SPs) in water and in 3D-HGs in phosphate buffer with a critical gelation concentration ranged between 1.5 and 2 mM (Figure 4…”
Section: Rgd Containing Peptidesmentioning
confidence: 99%
“…[ 197 ] When loaded with drug, these hydrogels exhibit sustained localized release profiles at the initial injection site, a feature that can be exploited to reduce off‐target side effects, improve drug efficacy, and allow for lowered total dosages. [ 198 ] Crucial for all medical applications, the structure and function of proteins delivery by MDPs do not show significant or unwanted changes conferred by the hydrogel, indicating high biocompatibility of the material. [ 199 ] Kumar et al.…”
Section: Hydrogels To Treat Dfusmentioning
confidence: 99%
“…Due to hydrogen bonding and other effects, tubustecan can cyclize and self-assemble to form tubular supramolecular nanostructures in an aqueous solution, which improves the water solubility of camptothecin and can be further used to load other hydrophobic drugs or molecules. In a representative study, they used a circular cell penetrating peptide iRGD to prepare a camptothecin-based tubustecan (TT6) through the coupling of biodegradable ethyl disulfonyl carbonate (etcSS linker) [45]. As shown in Figure 3, TT6 could first self-assemble to form a hollow tubular structure in an aqueous solution, and further assemble into a nanofiber hydrogel after the adding of PBS or DMEM medium.…”
Section: Camptothecin-based Low-molecular-weight Supramolecular Gelsmentioning
confidence: 99%